DILEMA ANTARA PEKERJAAN DAN STUDENT’ LEARNING: Strategi Coping Mahasiswa Sekolah Pascasarjana UIN Sunan Kalijaga - Imro'atul Muthohharoh (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2019)
This study discusses how the coping strategies of graduate students who have two roles, namely as students and workers. The purpose of this research is to find out the coping strategies of students who work in organizing, completing assignments and carrying out lectures. This type of research uses a qualitative descriptive approach with interview and observation techniques, that is, the researcher was directly involved (participatory). The informants in this study were five students of the 2018 social work class, Interdisciplinary Islamic Studies, UIN Sunan Kalijaga Yogyakarta. The results of this study indicate that the obstacles experienced by students who work are the difficulty in dividing time, changes in class schedules, and work assignments. The strategy used to overcome the obstacles that exist for the smooth running of the study is to use strategy focused coping, emotion focused coping, long-term coping, and short-term coping. Keywords: Strategy coping, students, work.